Pandemic: Globalization, roles of the State and international regimes - Deustua Caravedo, Alejandro (2020)
The intertwined global health and economic crisis which Covid-19 has generated shows the centrality of the role of the State in confronting both events as well as its vitalimportance in the performance of international organizations dealing with such problem. Multilateralism still depends on the State’s performance and not the other way around yet. The global crisis has also shown the need to reform the great majority of international regimes involved in it with the purpose of strengthening and enlarging their specificfunctions without risking such regimes with integral changes. Besides, the global nature of the pandemic has underlined the importance of geography in the efforts of tracing it. Such event implies the need of redefining the concept of globalization which underscores the delinkage of global processes from its territorial bases.